Bits and pieces : my mother, my brother, and me [large type] - Goldberg, Whoopi, 1955- (Blackstone Publishing, 2024)
If it weren't for her mother Emma, Caryn Johnson would have never become Whoopi Goldberg. When Whoopi lost her mother in 2010--and then her older brother, Clyde, five years later--she felt deeply alone. In this memoir, Whoopi shares many deeply personal stories of their lives together for the first time.